Avaliação geotecnológica da dinâmica e sucessão ecológica na fragmentação florestal na bacia hidrográfica do Rio Caxixe, ES - Pereira, Marcos Lima (2014)
The watershed of the Caxixe river spans a region with typical forest formations of the Atlantic, which undergoes strong human actions, mainly due to the landowner occupation process. In order to join efforts in protecting and conscious management of Atlantic Forest aimed to work with this study the spatio-temporal (1985-2010) evolution of dynamic, natural regeneration of forest fragments in the basin of river Caxixe, ES, for geotecnológica through analysis of satellite images of LANDSAT 5 TM. Structural analysis of forest fragments was based on the use of landscape metrics in Late-V 2.0 extension computational application ArcGIS 10.2. After the mapping of fragments verified for accuracy by the Kappa index (70.2%) and the value of Global Accuracy (86.29%). For demonstrating the relationship between the metric indexes of landscape ecology and natural regeneration fragment with greater potential for regeneration of watershed based mathematical model of multi-criteria analysis was studied. The metrics used for correlation were central area, proximity of the nearest neighbor central area, and total area. The woody plants with DBH = 5 cm were measured and identified, distributed in 18 plots (10 × 20m). Besides the floristic composition phytosociology, its diversity through the Shannon index (H '), evenness (J') and the floristic similarity were analyzed. The analyzes showed an increase of approximately 12.4% in forest cover past 25 years. The metrics analyzed, the total area and the core area of the fragment (30.53% each) were the most important variables. 133 species and 82 families were quantified. The richest families were individuals in Arecaceae, Asteraceae and Euphorbiaceae. In the fragment matrix Asteraceae, Lauraceae and Arecaceae family ones were the highest IVI. Fragment were regenerated in Arecaceae, Myrtaceae and Cyatheaceae It was observed that the parameters that most influenced IVI fragment matrix and dominance were often relative and absolute density in regenerated. Floristic diversity, calculated as H 'was 3.89 and for J' was 0.79, indicating medium to advanced stage of succession. Through similarity analysis evidenced the tendency to form three clusters by linking the fragment regenerates within the forest matrix. It has been found that regeneration was influenced by the proximity area and the neighbor, which explains the proximity of the fragment to regenerate the matrix. Metrics central area and full central area explain the diversity of species in the fragment matrix. Thus, the application of remote sensing techniques enabled the mapping of the spatio-temporal evolution and identification of regenerated fragments, being important for strategic planning aimed at the conservation and maintenance of areas of socio-economic and environmental importance. It is inferred that the metrics area, proximity of the neighboring area are correlated to the fragment regeneration process, being responsible for much of the regeneration potential.